Fa’aliyyatu Kitab al-‘Ashri fi Tarqiyyati al-Maharah al-Lughawiyyah - Siti Mahmudah (Postgraduate of IAIN Metro Lampung Indonesia, 2021)
The purpose of this study was to determine the effectiveness of the book al-'Ashri in improving the Arabic language skills of fourth grade students at SD Muhammadiyah Metro for the 2019/2020 academic year. For this reason, the researcher collected the required data using several data collection methods, namely tests, interviews, observation and documentation. After the data was collected, the researcher analyzed the data using the